2019
DOI: 10.1021/acssuschemeng.9b00754
|View full text |Cite
|
Sign up to set email alerts
|

Quasi-Solid-State Dye-Sensitized Solar Cells for Efficient and Stable Power Generation under Room Light Conditions

Abstract: Highly efficient quasi-solid-state dye-sensitized solar cells (QS-DSSCs) are fabricated using nanocomposite gel electrolytes and applied under room light conditions (200 lx). To obtain high energy conversion efficiency in QS-DSSCs, the important components of the DSSC are systematically optimized based on their performance in liquid-state DSSCs. It shows that the liquid cell using the 3-methoxypropionitrile-based cobalt electrolyte has higher efficiency (18.91%) than the cell using the acetonitrile-based elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 36 publications
0
43
0
Order By: Relevance
“…Several groups studied the replacement of the common acetonitrile solvent with higher-boiling solvents, usually causing a measurable, but not too signicant (<10%), drop in performance. 10,70 46 Nonetheless, a direct analysis of the effects of solvent choice on the stability of indoor DSCs has yet to be pursued. Intriguingly, rather than causing the malfunction of the photovoltaic cell, the drying of metal complex-based electrolytes leads to the formation of a solid-state hole conducting material, giving this class of electrolytes a signicant edge towards longterm durability over their I À /I 3 À counterparts.…”
Section: Stabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Several groups studied the replacement of the common acetonitrile solvent with higher-boiling solvents, usually causing a measurable, but not too signicant (<10%), drop in performance. 10,70 46 Nonetheless, a direct analysis of the effects of solvent choice on the stability of indoor DSCs has yet to be pursued. Intriguingly, rather than causing the malfunction of the photovoltaic cell, the drying of metal complex-based electrolytes leads to the formation of a solid-state hole conducting material, giving this class of electrolytes a signicant edge towards longterm durability over their I À /I 3 À counterparts.…”
Section: Stabilitymentioning
confidence: 99%
“…65,66,71 When adding zinc oxide nanocomposites, Venkatesan et al increased the conductivity of their cobalt complex-based gel electrolyte. 70 Wang et al and Venkatesan et al both performed stability tests of DSCs at room temperature under diffused light. 46,66 Venkatesan et al demonstrated that gelating the electrolyte with poly(ethylene oxide) increased the cells' durability.…”
Section: Dye-sensitized Solar Cells: Materials and Devicesmentioning
confidence: 99%
“…Among these polymers, the linear block copolymer has the simplest structure, so the investigation of its self-assembly behaviour is the most extensive and in-depth [1,2]. The self-assembly of block copolymers has a wide range of applications in materials, chemistry, nanoscience, and biomedicine [3,4]. However, in the conventional method, in order to in materials, chemistry, nanoscience, and biomedicine [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…The self-assembly of block copolymers has a wide range of applications in materials, chemistry, nanoscience, and biomedicine [3,4]. However, in the conventional method, in order to in materials, chemistry, nanoscience, and biomedicine [3,4]. However, in the conventional method, in order to obtain a better nanostructure morphology, the concentration of the block copolymer solution needs to be highly diluted [5,6], which limits its potential application.…”
Section: Introductionmentioning
confidence: 99%
“…The optimal redox for dim light operation is lower than that for sun-light environmental. [9][10][11] One of the other factors determining the performance of indoor To prepare bifacial dye-sensitized solar cells (DSSCs), the classical photoelectrode employing the main light-absorbing layer (ML) and scattering layer (SL) will encounter the scattering effect of SL to the rear-side incident light and, thereby, decrease the rear-side efficiencies. To solve this problem, the SL has always been removed for the fabrication of bifacial cells.…”
mentioning
confidence: 99%